The ability to manipulate plant glucosinolates and nutrients explains the better performance of Bemisia tabaci Middle East‐Asia Minor 1 than Mediterranean on cabbage plants. Issue 16 (30th June 2017) - Cui, Hongying; Guo, Litao; Wang, Shaoli; Xie, Wen; Jiao, Xiaoguo; Wu, Qingjun; Zhang, Youjun
Abstract: The performance of herbivorous insects is greatly affected by host chemical defenses and nutritional quality. Some herbivores have developed the ability to manipulate plant defenses via signaling pathways. It is currently unclear, however, whether a herbivore can benefit by simultaneously reducing plant defenses and enhancing plant nutritional quality. Here, we show that the better performance of the whitefly Bemisia tabaci Middle East‐Asia Minor 1 (MEAM1; formerly the "B" biotype) than Mediterranean (MED; formerly the "Q" biotype) on cabbage is associated with a suppression of glucosinolate (GS) content and an increase in amino acid supply in MEAM1‐infested cabbage compared with MED‐infested cabbage. MEAM1 had higher survival, higher fecundity, higher intrinsic rate of increase ( r m ), a longer life span, and a shorter developmental time than MED on cabbage plants. Amino acid content was higher in cabbage infested with MEAM1 than MED. Although infestation by either biotype decreased the levels of total GS, aliphatic GS, glucoiberin, sinigrin, glucobrassicin, and 4OH‐glucobrassicin, and the expression of related genes in cabbage, MED infestation increased the levels of 4ME‐glucobrassicin, neoglucobrassicin, progoitrin, and glucoraphanin. The GS content and expression of GS‐related genes were higher in cabbage infested with MED than with MEAM1. Our results suggest that MEAM1 performs better than MED on cabbage by manipulating host defenses and nutritional quality. Abstract : MEAM1 had higher survival, higher fecundity, higher intrinsic rate of increase ( r m ), a longer life span, and a shorter developmental time than MED on cabbage plants. Amino acid content was higher in cabbage infested with MEAM1 than MED, while the GS content and expression of GS‐related genes were higher in cabbage infested with MED than with MEAM1. Our results suggest that MEAM1 performs better than MED on cabbage by manipulating host defenses and nutritional quality.